Chernihiv Province Primary Schools of Agriculture in Late 19th-Early 20th Century - TERLETSKA, Ulyana Ivanivna (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article provides a brief analysis of the first primary schools of agriculturein Chernihiv province in late 19th and early 20th century.